2022
DOI: 10.3389/fmicb.2021.769891
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Biofunctional Properties of Phytofabricated Selenium Nanoparticles From Carica papaya Fruit Extract: Antioxidant, Antimicrobial, Antimycotoxin, Anticancer, and Biocompatibility

Abstract: The present study focused on phytofabrication of selenium nanoparticles (SeNPs) from Carica papaya extract and exploration of their multi-biofunctional features. Total phenolics and flavonoids of C. papaya fruit extract were determined as 23.30 ± 1.88 mg gallic acid equivalents and 19.21 ± 0.44 mg quercetin equivalents per gram, respectively, which suggested that C. papaya fruit extract could be a competitive reducing and stabilizing agent during phytofabrication of nanoparticles. UV–Vis and FTIR spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 84 publications
3
22
0
Order By: Relevance
“…The research on the nanoselenium synthesis using plant extracts is rare, because some problems still exist during the nanoselenium synthesis using plant extracts. For example, Vundela et al used Carica papaya extract to reduce sodium selenite and synthesized nanoselenium with a particle size ranging from 101 to 137 nm. As a result of its large particle size, the stability was low.…”
Section: Preparation Methods Of Nanoseleniummentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the nanoselenium synthesis using plant extracts is rare, because some problems still exist during the nanoselenium synthesis using plant extracts. For example, Vundela et al used Carica papaya extract to reduce sodium selenite and synthesized nanoselenium with a particle size ranging from 101 to 137 nm. As a result of its large particle size, the stability was low.…”
Section: Preparation Methods Of Nanoseleniummentioning
confidence: 99%
“…The stability of nanoselenium is closely related to the concentration, type, reducing power capacity, and application environment of reducing agents. The common nanoselenium reducing agents used in food are small-molecule peptides, amino acids, polysaccharides, organic acids, polyphenols, and flavonoids. , The stability of nanoselenium prepared by the reaction of the same selenium source with different reducing agents is different. Improper selection of reducing agents can lead to oxidation, flocculation, precipitation, and even failure to produce nanoselenium.…”
Section: Stability Of Nanoseleniummentioning
confidence: 99%
“…This process leads to an NP pro-oxidant behavior by free radical generation, on one side, which induces mitochondrial membrane disruption and, consequently, the leakage of mitochondrial proteins and endoplasmic reticulum (ER) stress on the other side [ 61 , 273 , 274 , 275 ]. Hence, several apoptotic molecular pathways which are regulated by SeNPs are activated or modulated, including TLR4/TRAF3/MFN1 (toll-like receptor-4/TNF receptor associated factor 3/mitofusin-1) [ 276 ]; p53, MAPK (mitogen-activated protein kinases) and AKT (protein kinase B) [ 277 , 278 , 279 ]; Bcl-2 family proteins [ 280 ]; ROS/JNK (c-Jun N-terminal kinase) [ 281 ]; PI3/Akt/mTOR (mammalian target of rapamycin); mTOR and NF-κB (nuclear factor kappa B) [ 282 ]; and caspase apoptotic pathways [ 268 , 280 , 283 ]. The regulation of these pathways is crucial for oncogenic signaling due to a considerable decrease in cellular proliferation and angiogenic signaling by obstructing the growth-promoting signaling in the vicinity of tumor cells.…”
Section: Properties Of Selenium Nanoparticlesmentioning
confidence: 99%
“…Thus, it may be useful for biological determinations to infer a lower dose of SeNPs. 134 Al-Otaibi et al (2022) attempted to create apigenin SeNPs (SeNPs-apigenin) using green synthesis and evaluated their anti-breast cancer activity. Multiple modified assays confirmed that SeNPs can inhibit MCF-7 cell viability and induce apoptosis in vitro .…”
Section: Introductionmentioning
confidence: 99%
“…Vundela et al (2022) tested C. papaya extract as a starting material for selenium nanoparticle (SeNP) production and analyzed the resulting SeNPs' biological effects. Here, the components of a fruit extract from C. papaya acted competitively to decrease nanoparticle size and stabilize them.…”
mentioning
confidence: 99%